HUMAN RIGHTS OF FOREIGNERS REFUSED ENTRY AND DETAINED AT AIRPORT TRANSIT ZONES: FROM NOVAK ĐOKOVIĆ SAGA TO THE ARBITRARY DETENTION OF H.G.D. - Kovačević, Nikola (Pravni zapisi, 2022)
The right to liberty and security of persons, as well as individual’s absolute right not to be ill-treated or sent to the territory of the State where one would face such risk, represent a cornerstone of refugee and migrant protection at all border crossings. However, regardless of the migration status of a foreigner arriving at the border control posts, an entire scope of human rights protects an individual from border police officers who exercise a State’s sovereignty in controlling entry, stay and expulsion from its territory. This undisputable right of the State is not an absolute one, and it has to be performed in line with the international human rights law, but also international refugee law. Inspired by the case of Novak Đoković, this paper deals with the legal status of foreigners who have been refused entry and detained at the airport transit zones. The practice at Belgrade airport will serve as a case study. The status of foreigners at the transit zone of the Nikola Tesla airport will be examined from the perspective of the right to liberty and security and the standards which arose from the practice of the European Court of Human Rights.